Marketing Strategy in Political Competition: A Case of the Campaign Team Samahuddin and La ntau - Riki, Riki; Moko, Wahdiyat; Djazuli, Atim (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
Abstract: This study aims to understand and explore the political marketing strategy of SAMATAU's campaign team in winning the political competition at the local level. Using a single Holistic interpretative case study (Robert K Yin, 2011), on the campaign team of Samahuddin - La Ntau, in this case as, the incumbent challenger as well as the winner of the Regent Election in 2017. The results of the study show that although the Samahuddin-La Ntau couple was categorized as a newcomer to the political competition, the campaign team of SAMATAU had several conditions and strategies in winning the competition including surveying and grouping voters, understand the characteristics and nature of voters, target actions, political image formations (framing), and also implementation of political programs that include political products, political campaigns, political venues, and political capital. In order to control the political programs that have been designed by the contestant, then the SAMATAU team conducts scheduled and unscheduled monitoring and evaluation. The implication of this study is that political marketing strategies give information to politicians, where this strategy is a systematic approach to help competitors in winning political competition.